Simultaneous determination of antiretroviral drugs in human hair with liquid chromatography-electrospray ionization-tandem mass spectrometry - Wu, Yan (J Chromatogr B Analyt Technol Biomed Life Sci, 2018)
The determination of the concentrations of antiretroviral drugs in hair is believed to be an important means for the assessment of the long-term adherence to highly active antiretroviral therapy. At present, the combination of tenofovir, lamivudine and nevirapine is widely used in China. However, there was no research reporting simultaneous determination of the three drugs in hair. The present study aimed to develop a sensitive method for simultaneous determination of the three drugs in 2-mg and 10-mg natural hair (Method 1 and Method 2). Hair samples were incubated in methanol at 37 °C for 16 h after being rinsed with methanol twice. The analysis was performed on high performance liquid chromatography tandem mass spectrometry with electronic spray ionization in positive mode and multiple reactions monitoring. Method 1 and Method 2 showed the limits of detection at 160 and 30 pg/mg for tenofovir, at 5 and 6 pg/mg for lamivudine and at 15 and 3 pg/mg for nevirapine. The two methods showed good linearity with the square of correlation coefficient more than 0.99 at the ranges of 416-5000 and 77-5000 pg/mg for tenofovir, 12-5000 and 15-5000 pg/mg for lamivudine and 39-50000 and 6-50000 pg/mg for nevirapine. They gave intra-day and inter-day coefficient of variation less than 15 % and the recoveries ranging from 80.6 to 122.3 % and from 83.1 to 114.4 %. Method 2 showed LOD and LOQ better than Method 1 for tenofovir and nevirapine and matched Method 1 for lamivudine, but there was high consistency between them in the determination of the three drugs in hair. The population analysis with Method 2 revealed that the concentrations in hair were decreased with the distance of hair segment away from the scalp for the three antiretroviral drugs.